Correcting for Body Surface Area Identifies the True Prevalence of Abdominal Aortic Aneurysm in Screened Women. (February 2019) - Jones, Gregory T.; Sandiford, Peter; Hill, Geraldine B.; Williams, Michael J.A.; Khashram, Manar; Tilyard, Murray W.; Hammond-Tooke, Graeme D.; Krysa, Jolanda; van Rij, Andre M.
Abstract : Objective: Recently, the prevalence of abdominal aortic aneurysm (AAA) using screening strategies based on elevated cardiovascular disease (CVD) risk was reported. AAA was defined as a diameter ≥30 mm, with prevalence of 6.1% and 1.8% in men and women respectively, consistent with the widely reported AAA predominant prevalence in males. Given the obvious differences in body size between sexes this study aimed to re-evaluate the expanded CVD risk based AAA screening dataset to determine the effect of body size on sex specific AAA prevalence. Methods: Absolute (26 and 30 mm) and relative (aortic size index [ASI] equals the maximum infrarenal aorta diameter (cm) divided by body surface area (m 2 ), ASI ≥ 1.5) thresholds were used to assess targeted AAA screening groups ( n = 4115) and compared with a self reported healthy elderly control group ( n = 800). Results: Male AAA prevalence was the same using either the 30 mm or ASI ≥1.5 aneurysm definitions (5.7%). In females, AAA prevalence was significantly different between the 30 mm (2.4%) and ASI ≥ 1.5 (4.5%) or the 26 mm (4.4%) thresholds. Conclusion: The results suggest the purported male predominance in AAA prevalence is primarily an artefact of body size differences. When aortic size is adjusted for body surface area there is only a modest sex difference in AAA prevalence. This observation has potential implications in the context of the ongoing discussion regarding AAA screening in women.